УЗГОДЖЕНЕ ТА ОПТИМІЗОВАНЕ ВІДПРАВЛЕННЯ ДЖЕРЕЛ, НАВАНТАЖЕНЬ ТА НАКОПИЧЕННЯ ЕНЕРГІЇ В КОМБІНОВАНИХ ЕЛЕКТРИЧНИХ ТА ОПАЛЮВАЛЬНИХ СИСТЕМАХ, ЩО ВРАХОВУЄ НЕВИЗНАЧЕНІСТЬ ТА ВІДПОВІДЬ ПОПИТУ - Lian, Ruiqing; You, Yiran; Li, Yong; Su, Shiwei (Інститут електродинаміки НАН України, Київ, 2021)
The problem of wind power abandonment in the north areas of China is serious, which is mainly caused by the uncertainty of wind power and the "thermoelectric coupling" characteristics of cogeneration units. Aiming at this problem, this paper establishes the optimal scheduling model of generation-load-storage coordination in the electrothermal joint system with the goal of minimizing the amount of wind power discarded and the total scheduling cost of the system. Firstly, the responsive electrical and thermal loads on the demand side are divided into three types according to their types, namely, translatable, transferrable and reducible, and the demand response models are constructed to improve the fineness of the optimization on the demand side. Then, the scenario method is used to solve the uncertainty problem of wind power. Meanwhile, the influence of the energy storage side on system scheduling is considered. Finally, the results based on examples verify the effectiveness of the proposed model in promoting the absorptive of wind power and improving the overall economic benefit of the system. References 23, figures 8, table 1.